Efficacy of Eribulin in Soft Tissue Sarcomas - Phillips, Edward; Jones, Robin L.; Huang, Paul; Digklia, Antonia (Frontiers in Pharmacology, 2022)
Soft tissue sarcomas (STS) are a highly heterogenous group of tumors with limited systemic therapy options. Eribulin, a synthetic analogue of halichondrin B, is a potent mitotic inhibitor. A phase 3 trial of previously treated advanced LPS and LMS demonstrated superiority of eribulin to dacarbazine. Eribulin appears to be particularly effective for liposarcomas. It has also been shown to be a safe and effective treatment alternative to doxorubicin in patients where doxorubicin is contraindicated. From retrospective studies, eribulin has demonstrated efficacy in patients with angiosarcoma, pleomorphic sarcomas, synovial sarcomas, rhabdomyosarcomas, angiosarcomas, and myxofibrosarcomas. Future areas of development include liposomal eribulin, which may provide increased efficacy and lower toxicity, and delineation of biomarkers of response and resistance, allowing better selection of patients for treatment.